Distal femoral fractures: A comparison between single lateral plate fixation and a combined femoral nail and plate fixation. Issue 2 (February 2022) - Garala, Kanai; Ramoutar, Darryl; Li, James; Syed, Farhan; Arastu, Mateen; Ward, Jayne; Patil, Sunit
Highlights: Nail plate fixation significantly reduces the chances of non-union compared to a single lateral plate fixation for distal femoral fractures even in more complex and difficult to manage fracture patterns. Nail plate fixation does not lead to any increase in morbidity or mortality. Nail plate fixation gives surgeons confidence for early weight bearing and therefore decreases immobility related morbidity. Nail plate fixation is of particular value in older patients with poor quality distal femur metaphyseal bone and subsequent metaphyseal comminution. Abstract: Objectives: Distal femoral fractures occur in patients with osteoporotic bone and also as a consequence of high energy trauma. The recognised treatment options include closed or open reduction of the fracture and fixation using a locking plate or a femoral nail. Both these fixation modalities have some drawbacks. There is a risk of metalwork failure with single lateral locking plates and limited distal fixation with intramedullary nails. Since January 2018, we started using augmented fixation of distal femoral fractures using a combination of a retrograde femoral nail and a lateral locking plate. This study compares the outcomes of single lateral femoral plating (SLP) and combined nail-plate fixation (NPF). Methods: This is a single centre retrospective case control study including all patients who sustained distal femoral fractures (OTA 33-A2, 33-A3, 33-C, 33-V3B and 33-V3D) over the study period. Outcomes for SLP were compared to NPF. The principal outcome measure was fracture union. Secondary outcome measures were reoperation rate, mortality and post-operative weight bearing status. Results: 67 distal femoral fractures were included in the study. 19 patients had peri‑prosthetic fractures. 40 were treated by SLP, 27 were managed with NPF.  23 (58%) patients in the SLP group were given instructions to non-weight bear or Toe touch weight bear for 6 weeks post-surgery compared to 1 (4%) in the NPF group ( p  = 0.000004). 7 (18%) patients treated with SLP had metalwork failure due to a non-union compared to none treated with NPF ( p  = 0.04). 11 fractures in the SLP group failed to unite compared to no non-unions in the NPF group ( p  = 0.01). These differences were magnified when assessing older (>50 years old) patients. Conclusions: Augmented fixation of distal femoral fractures using a nail plate fixation provided significantly higher union and enabled early weightbearing compared to single plate fixation. We recommend nail plate fixation for the treatment of distal femoral fractures, particularly in osteoporotic fractures.